Are Foreign Banks More Efficient than Domestic Banks? Case Study: Indonesia - Hutama, Gani Akbar; Prasetyo, Ahmad Danu (Journal of Business and Management, 2016)
Abstract.The aim of this study is to analyze and compare the efficiency of foreign and domestic conventional banks in Indonesia in 2013-2015 based on the BUKU 3 category regulated by Bank Indonesia and further sees the growth of those efficiencies by each month during the period of the study. The objects of this study are 9 foreign and 11 domestic conventional banks that operated in Indonesia in2013-2015. Data are retrieved from monthly financial reports of the sample. This study uses input-oriented Variable Return to Scale (VRS) Data Envelopment Analysis (DEA) model with intermediation approach to measure the technical efficiencies of the banks and Malmquist Index to investigate the growth of the efficiencies and also the monthly growth of the sample in the analysis period. Mann-Whitney test is used for hypothesis testing to examine the significance level of the efficiencies and its growth. DEA results shows that in aggregate, foreign banks are more efficient than domestic banks. The malmquist index results presents that domestic banks have higher average growth compared foreign banks in the period of analysis. Moreover, the sample’s performances in terms of monthly changes from the malmquist index experience fluctuation. However, there are no significant differences of both efficiency and its growth of foreign or domestic conventional banks in Indonesia during the period, meaning that both bank groups whether foreign or domestic banks in this study are operating in almost the same level.Keywords: foreign banks, domestic banks, efficiency, Data Envelopment Analysis, Malmquist Index